Influence of playing online video games on Filipino college students’ confidence in speaking English - Esteban, Allan Jay; Sung, Kiwan (Institute of Advanced Engineering and Science, 2025)
Online video games that require players to communicate in English provide opportunities for students to practice their language skills and overcome their fear of speaking in English. Unfortunately, the literature reveals an existing gap in investigating how such games can influence students’ confidence in speaking English, especially in the Philippine context. Therefore, this study surveyed 148 Filipino college English-as-a-second language (ESL) students to examine differences in their perceived confidence in speaking English depending on learner variables such as gender, time spent online gaming (TSOG), number of games played (NOGP), self-rated speaking proficiency (SRSP), and game interactivity.Using independent t-tests and one-way analysis of variance (ANOVA) analyses, results revealed statistically significant differences in the development of communication skills in English (DCSE) depending on the TSOG, willingness to communicate (WTC) in English depending on the NOGP, and enhancement of communication skills in English, active participation in class, and reduced anxiety in using English (RAUE) depending on the SRSP. This exploratory study indicates that online video games can be valuable tools in increasing English speaking confidence among Filipino college students. Further research is posited to understand the extent to which online games influence ESL learners’ speaking confidence in different educational and cultural contexts.